VD_FINDINFO Pron / 2011 / 7 vom 5. Januar 2011 - VD Tribunal cantonal (2011)
RÉCUSATION, EXPERT-ARBITRE, JUGE ARBITRE, TRIBUNAL ARBITRAL DU SPORT | 1 al. 1 C-Arb, 20 C-Arb, 3 C-Arb, 3 let. b C-Arb, 45 al. 1 C-Arb, 45 C-Arb, 346 CPC, 427 let. b CPC